Usage of Miniature Houses Built using Construction Materials in Engineering Educational Corporate Social Responsibility (CSR) Programs - Kevin Effendy; Tanti Octavia; Gunawan Budi Wijaya (International Journal of Industrial Research and Applied Engineering, 2021)
The demand for engineers in Indonesia has not been met with the number of professional engineers working in their respective fields. This is partly due to the low interest in engineering among students. Therefore, various programs are implemented by the government and companies to be able to introduce, educate and change perceptions on the field of engineering. This research was conducted to propose a Corporate Social Responsibility (CSR) program in order to meet these objectives. The proposed program is an educational program in the form of a workshop on residential construction using miniature houses built of real construction materials as demonstration and learning tools. The program is aimed at high school students in accordance with the goal of increasing public interests and the number of potential engineers, particularly in the field of civil engineering. The validation process of the proposed program is done by distributing questionnaires to construction companies and high school students as stakeholders in the program's execution. The validation results show that the proposed program is quite attractive to construction companies and high school students, including those who are not interested in the engineering field. The program is also deemed feasible and able to meet the goal of developing students' interest in engineering